Role of Majlis Ta'lim Mahabbatul Khadijah in Fostering Religious Education for Young Women in Kediri Sedayu Village, West Lombok - Wely Dozan; Sahirul Alim (Journal of Islamic Education Research, 2022)
This study examines the role of Majlis Ta'lim Mahabbatul Khadijah in fostering religious education for young women in Kediri Sedayu Village, West Lombok. The formulation of the main problem discussed is how the role of this majlis ta'lim or Islamic forum is to foster religious education for young women in Kediri Sedayu Village, West Lombok, and how the coaching process is. This study aims to find out how the role of this majlis ta'lim is to foster religious education for young women in Kediri Sedayu Village, West Lombok, and how the coaching process is. This study indicates several roles of the majlis ta'lim Mahabbatul Khadijah in fostering the religious education of young women in Kediri Village, West Lombok, as a place for teaching and learning to increase religious knowledge, a place to build networking, and a place of study for free. Meanwhile, the coaching process carried out by the majlis ta'lim in fostering the religious education of young women is by conducting study activities and practicing religious values ??such as holding clean Friday programs and social services. For example, clean Friday programs such as cleaning the prayer rooms or mosques in Kediri Sedayu Village, West Lombok. Meanwhile, the form of social service activities carried out by the Mahabbatul Khadijah majlis ta'lim such as providing donations to orphans and responding to natural disasters. This research implies that it is hoped that the majlis ta'lim Mahabbatul Khadijah will be able to contribute to society, especially to young women, in order to add insight into Islamic religious education.